Sustainability and Competition Law - Roman Inderst (Wirtschaftsdienst)
Abstract Sustainability goals are frequently achieved through cooperation between companies. However, this is often inadmissible under current competition law. So far, the competition authorities have had to limit their assessment of cooperations and mergers to the effects in the relevant market. The EU Commission has now explicitly taken up the issue of sustainability in the draft Horizontal Guidelines. It introduces exemptable cooperation on “sustainability cooperation”. Thus, the exchange of information on sustainable suppliers will be permissible, as will a joint campaign to promote sustainability awareness. The article discusses the possibilities and problems arising from this.